The Social Media as a Transformative Agent in the Electoral Process - DAVID N. ALMAREZ, DM; AJREE D. MALAWANI (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2016)
The growing use of social media in social interaction has changed the mode ofpolitical campaign in the Philippines. This research sought to determine the influences of social media in the presidential prefer-ences of netizens during the campaign period for the 2016 presidential elections in the Philippines. It also looked into the pattern of the preferences of respon-dents among the five presidential candidates for the 2016 presidential election. A total of 289 respondents participated out of 1210 visitors of the link used by the researchers. The data gathering started on February 9, 2016, the start of the presidential campaign period and ended on March 27, 2016 or a total of 47 days. The timeline for data gathering was constrained by the time limit that was set for this study. The results show that social media has no strong influence in the preferences of respondents with only 44% of the respondents saying that their presidential preferences were influenced by social media. However, 75.6% . The pattern of the preferences of respondents shows strong resemblance to some mock polls conducted by other groups in the Philippines during the cam-paign period. It is recommended to continue exploring the relevance of social media as a political tool for effective communication in politics and governance.